OPPORTUNITIES FOR DEVELOPING THE MORAL SPHERE OF PERSONALITY IN CHILDREN WITH INTELLECTUAL DISABILITY - Dubovskaya, Vera; Dmitrievskih, Ludmila; Ovsyannikova, Alyona (Revista Inclusiones, 2020)
This article analyzes scholarly approaches to the moral development of personality, describes the views of particular authors on this issue from the historical perspective; highlights and defines specific features and structural components of this notion; conducts a comparative analysis of moral development in case of normal ontogenesis and in case of intellectual disability. It also attempts to synthesize the existing scholarly approaches to the methods and conditions for effective moral development of children with intellectual disability in correlations with the structural components. In the main section of the article the authors provide a general overview of the correction methods facilitating moral development, and summarize the results of the experimental research of moral development in children with intellectual disability of the early school age.